Temporal patterns of visitation of birds and mammals at mineral licks in the Peruvian Amazon - Griffiths, Brian; Bowler, Mark; Gilmore, Michael; Luther, David (Dryad, 2020)
Mineral licks are key ecological resources for many species of birds and
mammals in Amazonia, providing essential dietary nutrients and clays, yet
little is known about which species visit and their behaviors at the
mineral licks. Studying visitation and behavior at mineral licks can
provide insight into the lives of otherwise secretive and elusive species.
We assessed which species visited mineral licks, when they visited, and
whether visits and the probability of recording groups at mineral licks
were seasonal or related to the lunar cycle. We camera trapped at 52
mineral licks in the northeastern Peruvian Amazon and detected 20 mammal
and 13 bird species over 6,255 camera nights. Generalized linear models
assessed visitation patterns and records of groups in association with
seasonality and the lunar cycle. We report nocturnal curassows (Nothocrax
urumutum) visiting mineral licks for the first time. We found seasonal
trends in visitation for the black agouti (Dasyprocta fuliginosa), red
howler monkey (Alouatta seniculus), blue-throated piping guan (Pipile
cumanensis), red brocket deer (Mazama americana), collared peccary (Pecari
tajacu) and tapir (Tapirus terrestris). Lunar trends in visitation
occurred for the paca (Cuniculus paca), Brazilian porcupine (Coendou
prehensilis) and red brocket deer. The probability of recording groups
(>1 individual) at mineral licks was seasonal and related to lunar
brightness for tapir. Overall, our results provide important context for
how elusive species of birds and mammals interact with these key
ecological resources on a landscape scale. The ecological importance of
mineral licks for these species can provide context to seasonal changes in
species occupancy and movement.
Study Site Fieldwork took place in the Maijuna community of Sucusari and
the Maijuna-Kichwa Regional Conservation Area (MKRCA), a 391,039-hectare
protected area in Loreto, Peru (El Peruano, 2015). This area is about 120
kilometers north by river of Iquitos, Peru (Fig 1). The title lands of the
Maijuna community encompasses 4,771 hectares and directly adjoin the MKRCA
to the south. The Sucusari River is a tributary of the Napo River and
terrestrial habitats include both upland terra firme primary rainforest
and floodplain forest. The mean annual temperature is 26oC and an average
precipitation of 3100 millimeters per year (Marengo, 1998). The wet season
consists of the months November to May, while the dry season is mainly
June to October in the Iquitos region (Espinoza Villar et al., 2009).
Camera Trapping We installed motion-activated camera traps (Bushnell
Aggressor, Boly Scout Guard) in the Sucusari River Basin at a sample of 52
mineral licks that were identified with the assistance of Maijuna hunters.
Starting in August, 2018, we visited all mineral licks, obtained GPS
coordinates, and placed camera traps in a series of four deployments, each
lasting at least 60 days to achieve even coverage of the whole basin (Fig
1). We left camera traps undisturbed at mineral licks for the entire
rotation period. Every 60 days cameras were removed, batteries and SD
cards changed, and cameras were rotated to new mineral licks (Kays et al.,
2020). During the third rotation most cameras went to previously unvisited
mineral licks, but some went to mineral licks that held a camera in August
but experienced camera malfunctions that prohibited the camera from
gathering 60 camera-nights of data.   The mineral licks in the
Sucusari River basin are generally characterized by waterlogged mud with
standing water and a face, which was often associated with a slope. The
area inside the lick was generally devoid of vegetation. The number of
camera traps placed in each mineral lick was determined by the size and
shape of the mineral lick, with the goal of recording all animal visits to
the mineral lick and meeting the assumption of perfect detection (all
medium and large-bodied animals entering the lick are captured). We set
cameras to record three rapid-fire images at each motion trigger with a
delay of two minutes between each set of images to avoid expending the
camera’s batteries. Cameras were set at a minimum of 50 centimeters from
the ground, facing the active face and entrance to the mineral lick,
following Tobler et al. (2009). We determined the location of the face
from signs of animal activity. Camera traps at mineral licks that did not
have a face were placed facing mud with signs of active animal activity.
We identified all medium and large sized mammal and bird species (weight
> 1 kg) in camera trap images (Blake, 1977; Emmons & Feer,
1997), removed empty images and organized data for analyses using
CameraBase v1.7 (Tobler, 2015). The number of individuals and species
identity in instances where multiple individuals appeared in the same
photograph was also recorded. Small-bodied birds and mammals, including
bats, were removed from analyses because they could rarely be identified
to species level. Mixed species flocks of parakeets were also not
considered for analysis since they commonly visited in groups of several
hundred individuals and could not be reliably identified to species level.
Images were sorted into independent visitation events, where multiple
visits by the same species within one hour of each other were considered
one visitation event, following Tobler et al. (2008).
Birds were identified separately from mammals, in a different sheet. An
independent event was considered two visits separated by one
hour.
Keywords: FOS: Earth and related environmental sciences; mineral lick; camera trap; mammal; Peru